Traditionally Used Lathyrus Species: Phytochemical Composition, Antioxidant Activity, Enzyme Inhibitory Properties, Cytotoxic Effects, and in silico Studies of L. czeczottianus and L. nissolia - Llorent-Martínez, Eulogio J.; Zengin, Gokhan; Fernández-de Córdova, María L.; Bender, Onur; Atalay, Arzu; Ceylan, Ramazan; Mollica, Adriano; Mocan, Andrei; Uysal, Sengul; Guler, Gokalp O.; Aktumsek, Abdurrahman (Frontiers in Pharmacology, 2017)
Members of the genus Lathyrus are used as food and in traditional drug formulations. In order to ﬁnd new sources of biologically-active compounds, chemical and biological profiles of two Lathyrus species (L. czeczottianus and L. nissolia) were investigated. Chemical profiles were evaluated by HPLC-ESI-MSn, as well as by their total phenolic and flavonoid contents. In addition, antioxidant, enzyme inhibitory, and cytotoxic effects were also investigated. Antioxidant properties were tested by using different assays (DPPH, ABTS, CUPRAC, FRAP, phosphomolybdenum, and metal chelation). Cholinesterases (AChE and BChE), tyrosinase, α-amylase and α-glucosidase were used to evaluate enzyme inhibitory effects. Moreover, vitexin (apigenin-8-C-glucoside) and 5-O-caffeoylquininic acid were further subjected to molecular docking experiments to provide insights about their interactions at molecular level with the tested enzymes. In vitro cytotoxic effects were examined against human embryonic kidney cells (HEK293) by using iCELLigence real time cell analysis system. Generally, L. czeczottianus exhibited stronger antioxidant properties than L. nissolia. However, L. nissolia had remarkable enzyme inhibitory effects against cholinesterase, amylase and glucosidase. HPLC-ESI-MSn analysis revealed that flavonoids were major components in these extracts. On the basis of these results, Lathyrus extracts were rich in biologically active components; thus, these species could be utilized to design new phytopharmaceutical and nutraceutical formulations.